Międzywojenny rozkwit prozy lesbijskiej w Polsce? Powieści "Przygoda w nieznanym kraju" Anieli Gruszeckiej, "Anetka" Marii Modrakowskiej i "Źródło samotności" Radclyffe Hall - Anna Artwich (Zagadnienia Rodzajów Literackich)
This article explores connections of newly discovered lesbian themes in three novels: Przygoda w nieznanym kraju [Adventure in an unknown country] by Aniela Gruszecka, Anetka by Maria Modrakowska and The Well of Loneliness by Radclyffe Hall. The article is organized in a way that makes it possible to highlight the similarities of motifs used in the texts, as well as deep thematic connections between Polish literary texts and the English novel. Although queer studies of the interwar period literature are not completely unexplored in the field of literary studies, these stories of non-heteronormative women have not yet been sufficiently touched upon. It was in that period that the Polish queer literature experienced a temporary flourishing — the analysis of the selected works of queer women’s depiction in modernist literature may show not only the continuity of the tradition of queer women’s writing in Poland, but also its linkage to the stream of European literature. The study’s aim is to dwell on the different representations of queer women outlined in these three literary works. While the first part of the article explores themes such as seclusion connected to queer childhood and unsuccessful attempts at forming relationships with women, the second part focuses on gothic motifs that play an important role in constructing the atmosphere of eeriness that surrounds the heroines.